Semiconducting metal oxides as sensors for environmentally hazardous gases - K. Wetchakun (2018)
This article extensively reviews the recent development of semiconductor metal oxide gas sensors for environmentally hazardous gases including NO2, NO, N2O, H2S, CO, NH3, CH4, SO2and CO2. The gas sensing properties of differently-prepared metal oxides and loaded metal oxides towards nine environmentally hazardous gases have been individually compared and digested. Promising materials for sensitive and selective detection of each hazardous gas have been identified. For instance, unloaded WO3nanostructures are the most promising candidates for NO2sensing while metal catalyst loaded WO3and gold-loaded SnO2sensors are among the most effective for NO and N2O sensing, respectively. Moreover, related gas-sensing mechanisms are comprehensively discussed. © 2011 Elsevier B.V. All rights reserved.